Glucose-regulated protein 78 (Grp78/BiP) is secreted by human oviduct epithelial cells and the recombinant protein modulates sperm–zona pellucida binding - Marín-Briggiler, Clara I.; González-Echeverría, María F.; Munuce, María J.; Ghersevich, Sergio; Caille, Adriana M.; Hellman, Ulf; Corrigall, Valerie M.; Vazquez-Levin, Mónica H. (Fertility and sterility, 2010)
To determine the secretion of Grp78 by human oviduct epithelial cells, its association to spermatozoa, and its involvement in gamete interaction. Prospective study. Basic research laboratory. Semen samples obtained from normozoospermic volunteers. Tubal tissue provided by patients undergoing hysterectomies. Oocytes collected from women undergoing IVF-ET. Analysis of Grp78 expression and secretion by oviductal tissue. Gamete incubation with recombinant Grp78 (rec-Grp78). Assessment of protein expression and secretion by immunohistochemistry and Western immunoblotting, respectively. Evaluation of rec-Grp78 binding to human spermatozoa by immunocytochemistry, and analysis of its effect upon gamete interaction using the hemizona assay. Grp78 was found in the surface of oviduct epithelial cells. Soluble Grp78 was detected in oviductal fluids from women in the periovulatory period and in oviductal tissue conditioned medium. Rec-Grp78 was able to bind to the sperm acrosomal cap, and its presence during gamete interaction led to a decrease in the number of spermatozoa bound to the zona pellucida (ZP). When calcium ions from the incubation medium were replaced by strontium, rec-Grp78 enhanced sperm–ZP interaction. Grp78 is expressed and secreted by oviduct epithelial cells. The protein would bind to the gametes and may modulate their interaction in a calcium-dependent manner.